Pembentukan karakter anak melalui kisah-kisah Nabi dalam Al-Qur’an - Dinda Rezika Shifa; Cantika Maharani; Nur Fadhillah Eka Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine how the stories of the prophets in the Qur’an can serve as an effective medium for character building in children from an early age. The research is motivated by the growing need for character education amidst the moral challenges of modern times, and by the strong potential of prophetic stories to convey Islamic values such as honesty, patience, responsibility, and monotheism. A qualitative approach was employed through a literature review method. The findings indicate that the stories of Prophet Musa (Moses), Ibrahim (Abraham), Muhammad, and Yunus (Jonah) contain relevant and applicable character values for children. By presenting moral teachings through storytelling, these narratives allow children to internalize values in an engaging and meaningful way. When delivered according to the child’s developmental stage, prophetic stories become an educational tool that effectively nurtures religious, responsible, and noble character. This study is expected to contribute to the development of Islamic value-based character education models in both family and formal educational settings.